Calculation of stationary electric fields in quasi-homogeneous media of multi-electrode composite electric radiators; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Evstigneev V. V. (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа